Differential diagnosis for multiple systemic inflammatory syndrome in children: clinical and laboratory clues - Bıcılıoğlu, Yüksel; Nalbant, Tuğçe; Çiçek, Alper; Ergönül, Esin; Gökalp, Gamze; Demir, Gülsah; Bardak, Şefika; Berksoy, Emel (The European Research Journal, 2023)
Objectives: We aimed to identify biochemical markers and clinical findings with high sensitivity and specificity that can be used in the differential diagnosis of patients suspected of having Multisystem Inflammatory Syndrome in Children (MISC) in the pediatric emergency department (PED). Moreover, we also examined early warning signs for predicting severe MIS-C patients requiring admission to intensive care unit (ICU). Methods: We conducted a retrospective analysis of patients presenting to the PED with suspected MIS-C. Patient records were assessed for initial complaints, physical examination findings, laboratory and ımaging test results, diagnoses, and follow-up plans. Patients diagnosed with MIS-C were categorized as the MIS-C group, while others were categorized as the non-MIS-C group. Comparisons were made between these two groups. Results: A total of 266 patients were included, with 68 diagnosed with COVID-19-associated MIS-C, including 20 monitored in the pediatric ICU. MIS-C patients had higher mean age, hospitalization, and ICU admission rates compared to non-MIS-C. MIS-C group showed higher prevalence of respiratory symptoms, hematological involvement, and shock. We observed lymphopenia, thrombocytopenia, hyponatremia, and elevated levels of blood C-reactive protein (CRP), procalcitonin, triglycerides, troponin, Brain Natriuretic Peptide (BNP), D-dimer, and fibrinogen in the MIS-C group. ICU patients had higher procalcitonin, aspartate aminotransferase, alanine aminotransferase, triglycerides, troponin, BNP, and ferritin levels, and lower sodium levels. Conclusions: COVID-19-associated MIS-C group had higher rates of respiratory symptoms, hematological involvement, and shock. Lymphopenia, thrombocytopenia, elevated CRP, and D-dimer can guide MIS-C differential diagnosis. Additional tests (procalcitonin, troponin, BNP, triglycerides, ferritin) are recommended for high-suspicion cases. Patients with elevated BNP levels may require ICU admission.